Hesperidin identified from Citrus extracts potently inhibits HCV genotype 3a NS3 protease - Mahim Khan; Waqar Rauf; Fazal-; Moazur Rahman; Shoaib Iqbal; Aamir Shehzad; Mazhar Iqbal (BMC, 2022)
Abstract Background Hepatitis C virus infection is the main cause of liver ailments across the globe. Several HCV genotypes have been identified in different parts of the world. Effective drugs for combating HCV infections are available but not affordable, particularly to infected individuals from resource-limited countries. Hence, cost-effective drugs need to be developed against important HCV drug targets. As Citrus fruits naturally contain bioactive compounds with antiviral activities, the current study was designed to identify antiviral inhibitors from Citrus fruit extracts against an important drug target, NS3 protease, of HCV genotype 3a which is found predominantly in South Asian countries. Methods The full-length NS3 protease alone and the NS3 protease domain in fusion with the cognate NS4A cofactor were expressed in Escherichia coli, and purified by chromatographic techniques. Using the purified protein as a drug target, Citrus extracts were evaluated in a FRET assay, and active ingredients, identified using ESI-MS/MS, were docked to observe the interaction with active site residues of NS3. The best interacting compound was further confirmed through the FRET assay as the inhibitor of NS3 protease. Results Fusion of the NS3 protease domain to the NS4A cofactor significantly improved the purification yield, and NS3-NS4A was functionally more active than the full-length NS3 alone. The purified protein (NS3-NS4A) was successfully employed in a validated FRET assay to evaluate 14 Citrus fruit extracts, revealing that the mesocarp extract of Citrus paradisi, and whole fruit extracts of C. sinesis, C. aurantinum, and C. reticulata significantly inhibited the protease activity of HCV NS3 protease (IC50 values of 5.79 ± 1.44 µg/mL, 37.19 ± 5.92 µg/mL, 42.62 ± 6.89 µg/mL, and 57.65 ± 3.81 µg/mL, respectively). Subsequent ESI-MSn analysis identified a flavonoid, hesperidin, abundantly present in all the afore-mentioned Citrus extracts. Importantly, docking studies suggested that hesperidin interacts with active site residues, and acts as a potent inhibitor of NS3 protease, exhibiting an IC50 value of 11.34 ± 3.83 µg/mL. Conclusions A FRET assay was developed using NS3-NS4A protease, which was successfully utilized for the evaluation of Citrus fruit extracts. Hesperidin, a compound present in the Citrus extracts, was identified as the main flavonoid, which can serve as a cost-effective potent inhibitor of NS3 protease, and could be developed as a drug for antiviral therapy against HCV genotype 3a.